The Role of Activin A levels, Body Mass Index and Beta-Human Chorionic Gonadotropin in Ectopic Pregnancies and Missed Abortions – A Study on a Group of Iraqi Women - Rafak, Hussein M.; Rasheed , Manal K.; Salih, Farah A. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Activin A (ACV-A), a member of the transforming growth factor-beta (TGF-beta) superfamily that regulates follicular growth hormone (FSH) secretion and initiates intracellular signaling pathways, is essential to reproductive regulation. ACV-A is involved in regulating cellular proliferation, differentiation, apoptosis, and homeostasis, among other biological processes. The pituitary gland, the gonads, and other organs all secrete ACV-A, which is made up of two beta A (βA) subunits. Objectives: To compare the serum concentrations of ACV-A in women diagnosed with missed abortion (MA) or ectopic pregnancy (EP) with those of healthy controls. Methods: The study was conducted in the gynecology departments of the Medical City - Baghdad Teaching Hospital and Al-Kut Obstetrics and Gynecology Hospital from October 2023 to January 2024. A total of 120 women aged between 18 and 45 years participated in the study; An ectopic pregnancy was diagnosed in 30 of them, 30 had a missed miscarriage, and the remaining 60 were considered a control group. ACV-A and beta-human chorionic gonadotropin (β-HCG) levels were measured by the enzyme-linked immunosorbent assay (ELIZA) method. Results: The control group had a significantly lower mean ± SD of ACV-A (773.6 ± 130.26 pg/ml) in comparison to the EP group (1408.1 ± 219.02 pg/ml) and the MA group (1200.9 ± 199.31). In addition, patients in the ectopic group had a significantly lower mean± SD of ACV-A than patients in the missed abortion group. Conclusion: Serum Activin A levels can be used as an indicator of ectopic pregnancy and missed abortions. A novel biomarker for evaluating women who have an ectopic pregnancy could be the level of HCG in their serum at a cutoff value of greater than 236 ng/ml.